Modelling hydrology and water quality in a mixed land use catchment and eutrophic lake: Effects of nutrient load reductions and climate change. (November 2018) - Me, Wang; Hamilton, David P.; McBride, Christopher G.; Abell, Jonathan M.; Hicks, Brendan J.
Abstract: The objective of this study was to combine a catchment model with a one–dimensional lake water quality model to simulate the trophic state of a eutrophic shallow lake in response to nutrient load reductions and climate change. The catchment and lake models gave satisfactory performance in simulating observed data, indicating that the key processes that affect nutrient loads and lake trophic status were adequately represented. Simulating removal of nutrients by reducing fertiliser applied to farmland or irrigated wastewater had minor effects on nutrient concentrations in the lake, but simulations using a projected climate for 2090 showed a major impact on nutrients and water quality. This overarching effect indicated that polymictic lakes may be particularly vulnerable to eutrophication associated with climate change due to increased internal nutrient loading, which will lead to a biological response of increased algal biomass, while changes in external loads will have lesser relative impact. Highlights: Combined climate–catchment–lake modelling reveals flow–on effects to a polymictic lake. Small water quality improvement with large nutrient reductions in one sub–catchment. Minor lake response to climate change effects from changes in catchment processes. Major lake response to climate change due to effects on stratification. Climate change has potential to confound restoration of shallow eutrophic lakes.